2013
DOI: 10.1371/journal.pone.0063413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Patterns of Bacteria from Milkmen and Cows with Clinical Mastitis in and around Kampala, Uganda

Abstract: BackgroundIdentification of pathogens associated with bovine mastitis is helpful in treatment and management decisions. However, such data from sub-Saharan Africa is scarce. Here we describe the distribution and antimicrobial susceptibility patterns of bacteria from cows with clinical mastitis in Kampala, Uganda. Due to high concern of zoonotic infections, isolates from milkmen are also described.Methodology/Principal FindingsNinety seven milk samples from cows with clinical mastitis and 31 nasal swabs from mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 31 publications
10
104
4
Order By: Relevance
“…This is in contrast to the report by Kateete et al, (2013) that isolated Lactobacillus species from only 9% of milk samples analysed. The detection of Lactobacillus species in the studied milk products is indicative of its use as starter cultures in the production /fermentation of milk and milk products (Medicinal Veterinary Animal Health, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the report by Kateete et al, (2013) that isolated Lactobacillus species from only 9% of milk samples analysed. The detection of Lactobacillus species in the studied milk products is indicative of its use as starter cultures in the production /fermentation of milk and milk products (Medicinal Veterinary Animal Health, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…The farm result was slightly lower than 15.5% (51/328), [31] in around Addis Ababa; 17.2%, [32] in Egypt and 19.5%, [33] who isolated S. aureus strains from human and animal sources. Of the farm sample 5/42 (11.9%), 1/9 (11.1%), 0 (0.0%), 3/9 (33.3%), 1/9 (11.1%), and 3/9 (33.3%); udder milk, tank milk, polled bucket swab, tank swab, polled hand and nasal swab, respectively, were positive for S. aureus The findings of the present study revealed a lower proportional rate than 75% in 220 bovine bulk milk reported in [34], 68% (15/22) in [5], 61.3% (49/80) in [35], and 40% (32/81) in [36], but higher than [37] which was 8% (8/100) in udder milk and 10% (10/100) in tank milk. Also the present result shows the proportion of S. aureus in polled farm nasal swab 3/9 (33.3%) was higher than [38], 4/31(13%) and [33] who reported 20% from nasal swabs of diseased human.…”
Section: Citationmentioning
confidence: 43%
“…At present, little is known about the occurrence of molecular types and antimicrobial resistance (AMR) profile of S. aureus isolates from bovine subclinical mastitis in India. Changes in mastitis isolate profiles influenced by setting have been reported earlier (3), which again emphasizes the need for periodic evaluation of S. aureus in terms of virulence and AMR. Currently, penicillin, erythromycin, and tetracycline are frequently used for the treatment of mastitis.…”
Section: Introductionmentioning
confidence: 53%